Preparation method of PET (Polyethylene Terephthalate) resin film for solar cell backboard

By applying a composite coating with a specific ratio on the PET resin film of the solar cell back panel, the problems of aging and insufficient waterproof performance in long-term outdoor use are solved, and high weather resistance, ultraviolet resistance and waterproof performance are improved, and the service life of the components is extended.

CN119613789APending Publication Date: 2025-03-14ZHEJIANG TAIYANG LITHIUM BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411944289.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The PET resin film of the existing solar cell back panel is prone to aging and yellowing during long-term outdoor use, and has insufficient waterproof performance, making it difficult to meet the requirements for use in harsh environments.

Method used

Using a composite coating coated on the surface of the PET resin plate, including marinic acid modified rosin resin, nanosilica modified epoxy resin, hydrophobic modification liquid and anti-UV agent, a dense coating is formed to improve weather resistance, UV resistance and waterproof properties through an optimized composition ratio and preparation process.

Benefits of technology

It significantly improves the weather resistance and UV resistance of PET resin film, enhances waterproof performance, extends the service life of solar cell modules, and has a simple and controllable preparation process, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213273020000101
    Figure BDA0005213273020000101
Patent Text Reader

Abstract

The invention discloses a preparation method of a PET resin film for a solar cell backboard, the PET resin film comprises a PET resin plate and a composite coating, the composite coating comprises the following components by weight: 15-30 parts of maleic acid modified rosin resin, 20-30 parts of nano silica modified epoxy resin, 10-20 parts of a hydrophobic modification liquid, 14-18 parts of an anti-ultraviolet agent, and 8-12 parts of an emulsifier. The preparation method comprises the following steps: S100, preparing a coating stock solution of the composite coating; s200, the PET resin plate is coated with the coating stock solution; and S300, drying to obtain the PET resin film for the solar cell PET backboard. According to the invention, the weather resistance and the ultraviolet resistance of the PET resin film are remarkably improved through the optimal component ratio and the specific preparation process, and the technical problem that the existing solar cell backboard is easy to age and yellow in the long-term outdoor use process is solved; and meanwhile, the compounding design of the hydrophobic modified liquid is adopted, so that the waterproof performance of the PET resin film is effectively enhanced, and the service life of the solar cell module is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solar cells, and in particular to the technical field of solar cell backplane film materials. Background Art

[0002] The solar cell backplane is an important component of the solar cell module, and its main function is to provide mechanical support, electrical insulation and environmental protection for the solar cell module. At present, PET resin film has become one of the most commonly used materials for solar cell backplanes due to its good mechanical properties and low cost. However, the PET resin film in the prior art has many problems in practical application: the traditional PET resin film is prone to aging and degradation when exposed to the outdoor environment for a long time, especially under strong ultraviolet radiation, the PET molecular chain will break, resulting in the degradation of material performance, yellowing, cracking and other phenomena; the commonly used anti-ultraviolet agents on the market are of a single type, and have poor compatibility with the PET substrate, and are prone to precipitation and migration; the surface of the traditional PET resin film is highly hydrophilic, and it is easy to absorb water in a humid environment, resulting in interlayer peeling and electrical performance degradation; the composite coating in the prior art often adopts a single resin system, which has insufficient bonding strength with the PET substrate, and the internal structure of the coating is loose, which is prone to cracking and peeling.

[0003] With the rapid development of solar power generation technology, photovoltaic modules are developing towards longer life and higher reliability, which puts forward higher requirements for backplane materials, especially in application scenarios in harsh environments such as deserts and seaside, requiring backplane materials to have excellent weather resistance, UV resistance and waterproof performance. The preparation method of PET resin film in the prior art, although it improves the weather resistance of the material to a certain extent, the modification scheme often adopted is costly, the waterproof effect still needs to be improved, and its process is complicated, which is not conducive to large-scale production. Therefore, it is urgent to develop a method for preparing PET resin film with excellent weather resistance, UV resistance and waterproof performance to meet the use requirements of solar cell modules in various harsh environments.

[0004] The PET resin film of the present invention is prepared by coating a composite coating of a specific ratio on the surface of a PET resin plate, wherein the maleic acid modified rosin resin provides excellent substrate adhesion and weather resistance, the nano-silicon dioxide modified epoxy resin enhances the mechanical strength and wear resistance of the coating, the specially prepared hydrophobic modification liquid gives the coating a lasting waterproof property, the compounded anti-ultraviolet agent system effectively blocks the destructive effect of ultraviolet rays on the substrate, and the synergistic effect of multiple components significantly improves the comprehensive performance of the PET resin film. At the same time, the preparation process adopted by the present invention is simple and controllable, and the compactness and uniformity of the coating structure are ensured through optimized coating and curing processes, so that the product has good production stability and repeatability, and is suitable for industrial-scale production. Summary of the invention

[0005] The purpose of the present invention is to overcome the technical problem that the existing solar cell back sheet is easy to age and yellow during long-term outdoor use. Through the optimal component ratio and specific preparation process, the weather resistance and UV resistance of the PET resin film are significantly improved; at the same time, the composite design of the hydrophobic modification liquid is adopted to effectively enhance the waterproof performance of the PET resin film and extend the service life of the solar cell module.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a PET resin film for a solar cell backplane, wherein the PET resin film comprises a PET resin plate and a composite coating, wherein the composite coating comprises the following components in parts by weight:

[0008] 15-30 parts of maleic acid modified rosin resin;

[0009] 20-30 parts of nano-silicon dioxide modified epoxy resin;

[0010] 10-20 parts of hydrophobic modification liquid;

[0011] 14-18 parts of anti-ultraviolet agent;

[0012] Emulsifier 8-12 parts;

[0013] The preparation method comprises:

[0014] S100: preparing a coating stock solution for a composite coating;

[0015] S200: applying the coating stock solution to the PET resin plate;

[0016] S300: Drying to obtain a PET resin film for a solar cell PET backplane.

[0017] The preparation of the coating stock solution specifically includes:

[0018] S101: adding anhydrous ethanol or butyl acetate to a constant temperature mixer, and then adding a mixture of maleic acid-modified rosin resin and nano-silica-modified epoxy resin to obtain a mixed solution A;

[0019] S102: Adding an emulsifier, a hydrophobic modification liquid, and an anti-ultraviolet agent to the mixed solution A to obtain a coating stock solution.

[0020] The hydrophobic modified liquid is obtained by compounding modified silicon dioxide, calcium gluconate and ultrapure water.

[0021] The anti-ultraviolet agent is obtained by compounding a UV series ultraviolet absorber and a BP series ultraviolet absorber.

[0022] Wherein, the emulsifier is selected from one of polyethylene glycol, Tween 80 and carboxymethyl cellulose.

[0023] The hydrophobic modified liquid is obtained by compounding modified silicon dioxide, calcium gluconate and ultrapure water, specifically mixing them in a ratio of 5:1:94.

[0024] The anti-ultraviolet agent is compounded by UV series ultraviolet absorber and BP series ultraviolet absorber, specifically, ultraviolet absorber UV-9 whose main component is 2-hydroxy-4-methoxybenzophenone and ultraviolet absorber BP-2 whose main component is 2,2',4,4'-tetrahydroxybenzophenone are compounded in a ratio of 1.2:1.

[0025] The modified silicon dioxide is obtained by co-modifying nano silicon dioxide with tridecafluorooctyltrimethoxysilane, vinyltrimethoxysilane and methacryloxyethyltrimethylammonium chloride.

[0026] The preparation steps include:

[0027] S401: Under nitrogen blowing, 1-5 parts by mass of nano-silicon dioxide is transferred into a solid phase synthesis tube and anhydrous ethanol is added;

[0028] S402: adjusting the pH value of the solution in the synthesis tube to 4-5 by dropwise adding dilute acetic acid, adding 1-5 parts by mass of ten-fold trifluorooctyltrimethoxysilane and 2-5 parts by mass of vinyltrimethoxysilane, respectively, and reacting at 50-60° C. for 6-8 hours to obtain co-grafted silica;

[0029] S403: adding deionized water or anhydrous ethanol to the synthesis tube to alternately wash the co-grafted silica for 2-3 rounds to remove the reaction reagents, adding anhydrous ethanol and blowing the co-grafted silica evenly with nitrogen;

[0030] S404: The pH value of the solution in the synthesis tube is adjusted to 4-5 by dropping dilute acetic acid, 2-5 parts by mass of methacryloyloxyethyl trimethyl ammonium chloride is added, and the reaction solution is discarded after reacting at 50-60°C for 4-5 hours, and deionized water or anhydrous ethanol is added to the synthesis tube for 2-3 rounds of alternating washing, and nitrogen is blown for 1-1.5 hours, and then the tube is transferred to a 60°C vacuum drying oven for drying to obtain modified silica.

[0031] The drying steps specifically include:

[0032] S301: using a cast coating method or a roller coating method, the coating stock solution is repeatedly coated three times on the surface of the PET resin plate;

[0033] S302: After coating, pre-dry in a fume hood for 30 minutes;

[0034] S303: Curing at 150°C for 30 minutes to form a dense coating.

[0035] The invention significantly improves the weather resistance and anti-ultraviolet performance of the PET resin film by designing a composite coating with an optimal ratio. The synergistic effect of the maleic acid-modified rosin resin and the nano-silicon dioxide-modified epoxy resin in the composite coating enhances the bonding force between the coating and the PET resin plate, thereby improving the overall stability of the product.

[0036] The present invention adopts the compounding technology of hydrophobic modified liquid, and effectively enhances the waterproof performance of PET resin film by compounding modified silicon dioxide, calcium gluconate and ultrapure water in a specific ratio. The modified silicon dioxide is co-modified with three silane coupling agents, which gives the material excellent hydrophobic properties, so that the product has good hydrolysis resistance during long-term outdoor use.

[0037] The present invention selects UV series and BP series ultraviolet absorbers as anti-ultraviolet agents. The synergistic effect of the two absorbers significantly improves the anti-ultraviolet performance of the PET resin film. By controlling the optimal ratio of UV-9 and BP-2, the aging and yellowing of the PET resin film during long-term use is effectively prevented.

[0038] The preparation process of the invention is simple, easy to control, does not require special equipment, and is suitable for industrial production. The coating is carried out by cast coating or roller coating, and a dense coating is formed by pre-drying and curing processes, thereby ensuring the stability and consistency of product quality. DETAILED DESCRIPTION

[0039] The purpose of the present invention is to provide a high-performance solar cell backplane PET resin film, which has excellent weather resistance, UV resistance and waterproof performance, and can effectively solve the problem that the existing solar cell backplane is easy to age and yellow during long-term outdoor use. Through the preferred component ratio and specific preparation process, the PET resin film can still maintain excellent performance stability under high temperature and high humidity environment; the composite design of hydrophobic modification liquid is adopted to significantly improve the waterproof performance of the PET resin film; the synergistic effect of UV series and BP series ultraviolet absorbers is utilized to greatly enhance the anti-ultraviolet performance of the product; and the overall performance of the material is further improved through the co-modification process of multiple silane coupling agents of modified silica. The preparation process of the present invention is simple and controllable, suitable for industrial production, and the product has stable performance and long service life. It aims to provide a solar cell backplane material with excellent performance and reliable application.

[0040] To achieve the above-mentioned purpose, the method adopted by the present invention is: to provide a method for preparing a PET resin film for a solar cell backplane, wherein the PET resin film comprises a PET resin plate and a composite coating. Wherein, the composite coating comprises the following components by weight: 15-30 parts of maleic acid modified rosin resin, 20-30 parts of nano-silicon dioxide modified epoxy resin, 10-20 parts of hydrophobic modification liquid, 14-18 parts of anti-ultraviolet agent, and 8-12 parts of emulsifier; the present invention achieves the synergistic effect of each group through the preferred component ratio and specific preparation process. Wherein, the combination of maleic acid modified rosin resin and nano-silicon dioxide modified epoxy resin enhances the bonding force between the coating and the substrate; the special design of the hydrophobic modification liquid enhances the waterproof performance of the product; the compounding of UV series and BP series ultraviolet absorbers significantly improves the anti-ultraviolet performance of the PET resin film; the multi-silane coupling agent co-modification process further optimizes the overall performance of the material.

[0041] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0042] [Example 1]

[0043] A method for preparing a PET resin film for a solar cell backplane, the raw material parts used below are by mass, and the specific steps are as follows:

[0044] S1: Preparation of modified silica

[0045] Under nitrogen blowing, 1 part of nano-silica was transferred into a solid phase synthesis tube and 100 parts of anhydrous ethanol were added, dilute acetic acid was added dropwise to adjust the pH value to 4.5, 2 parts of tridecafluorooctyltrimethoxysilane and 3 parts of vinyltrimethoxysilane were added in sequence, and the mixture was reacted at 55°C for 7 hours to obtain co-grafted silica;

[0046] Wash the co-grafted silica with deionized water and anhydrous ethanol alternately for 3 rounds, add anhydrous ethanol and blow it evenly with nitrogen;

[0047] The pH value was adjusted to 4.5, 3 parts of methacryloyloxyethyl trimethyl ammonium chloride were added, the mixture was reacted at 55°C for 4.5 hours, the reaction solution was discarded, and the mixture was washed alternately with deionized water and anhydrous ethanol for 3 rounds, and then dried in vacuum at 60°C after blowing with nitrogen for 1.2 hours to obtain modified silica;

[0048] S2: Preparation of hydrophobic modification solution

[0049] 5 parts of modified silicon dioxide, 1 part of calcium gluconate and 94 parts of ultrapure water were mixed and ultrasonically dispersed for 30 minutes to obtain a hydrophobic modified liquid;

[0050] S3: Preparation of UV-resistant agent

[0051] Mix UV-9 and BP-2 in a mass ratio of 1.2:1, wherein UV-9 is 9 parts and BP-2 is 7.5 parts, and stir evenly at 70° C. to obtain an anti-ultraviolet agent;

[0052] S4: Preparation of coating stock solution

[0053] Add 200 parts of anhydrous ethanol to a constant temperature mixer, add 25 parts of maleic acid modified rosin resin and 25 parts of nano-silica modified epoxy resin in sequence, and stir at 60°C for 2 hours to obtain a mixed solution A; add 10 parts of polyethylene glycol (as an emulsifier), 15 parts of hydrophobic modification liquid, and 16.5 parts of anti-ultraviolet agent in sequence to the mixed solution A, and stir at 50°C for 1 hour to obtain a coating stock solution;

[0054] S5: Coating process

[0055] The coating stock solution was evenly coated on the surface of the PET resin plate by cast coating method and pre-dried in a fume hood for 30 minutes;

[0056] Repeat the coating operation three times;

[0057] Finally, the film was cured at 150° C. for 30 minutes to obtain a solar cell backplane PET resin film with a dense composite coating.

[0058] [Example 2]

[0059] S1: Preparation of modified silica

[0060] Under nitrogen blowing, 1 part of nano-silica was transferred into a solid phase synthesis tube and 120 parts of anhydrous ethanol were added, dilute acetic acid was added dropwise to adjust the pH value to 4, 2 parts of tridecafluorooctyltrimethoxysilane and 3 parts of vinyltrimethoxysilane were added in sequence, and the mixture was reacted at 60°C for 8 hours to obtain co-grafted silica;

[0061] Wash the co-grafted silica with deionized water and anhydrous ethanol alternately for 2 rounds, add anhydrous ethanol and blow it evenly with nitrogen;

[0062] The pH value was adjusted to 4, 3 parts of methacryloyloxyethyl trimethyl ammonium chloride were added, and the mixture was reacted at 60° C. for 5 hours, the reaction solution was discarded, and the mixture was washed alternately with deionized water and anhydrous ethanol for 2 rounds, and then dried in a vacuum at 60° C. after blowing with nitrogen for 1.5 hours to obtain modified silica;

[0063] S2: Preparation of hydrophobic modification solution

[0064] 5 parts of modified silicon dioxide, 1 part of calcium gluconate and 94 parts of ultrapure water were mixed and ultrasonically dispersed for 45 minutes to obtain a hydrophobic modified liquid;

[0065] S3: Preparation of UV-resistant agent

[0066] Mix UV-9 and BP-2 in a mass ratio of 1.2:1, wherein UV-9 is 8 parts and BP-2 is 6.7 parts, and stir evenly at 75° C. to obtain an anti-ultraviolet agent;

[0067] S4: Preparation of coating stock solution

[0068] Add 180 parts of butyl acetate to a constant temperature mixer, add 20 parts of maleic acid-modified rosin resin and 28 parts of nano-silica-modified epoxy resin in sequence, and stir at 65° C. for 2.5 hours to obtain a mixed solution A;

[0069] To the mixed solution A, 12 parts of Tween 80 (as an emulsifier), 18 parts of a hydrophobic modification liquid, and 14.7 parts of an anti-ultraviolet agent were added in sequence, and the mixture was stirred at 55° C. for 1.5 hours to obtain a coating stock solution;

[0070] S5: Coating process

[0071] The coating stock solution was evenly coated on the surface of the PET resin plate by roller coating and pre-dried in a fume hood for 30 minutes;

[0072] Repeat the coating operation three times;

[0073] Finally, the film was cured at 150° C. for 30 minutes to obtain a solar cell backplane PET resin film with a dense composite coating.

[0074] [Comparative Example 1]

[0075] A method for preparing a PET resin film for a solar cell backplane, the raw material parts used below are by mass, and the specific steps are as follows:

[0076] S1: Preparation of modified silica

[0077] Under nitrogen blowing, 1 part of nano-silica was transferred into a solid phase synthesis tube and 100 parts of anhydrous ethanol were added, and only 2 parts of tridecafluorooctyltrimethoxysilane were added for single modification, and the reaction was carried out at 55°C for 7 hours;

[0078] After washing with deionized water and anhydrous ethanol for 2 rounds, the product was dried under vacuum at 60 °C to obtain single modified silica;

[0079] S2: Preparation of hydrophobic modification solution

[0080] 5 parts of the single modified silica were mixed with 95 parts of ultrapure water and dispersed by ultrasonic for 30 minutes to obtain a hydrophobic modified liquid (without adding calcium gluconate);

[0081] S3: Preparation of UV-resistant agent

[0082] Only 8 parts of UV-9 were used as anti-ultraviolet agent (the compound design of UV-9 and BP-2 was not adopted);

[0083] S4: Preparation of coating stock solution

[0084] Add 200 parts of anhydrous ethanol to a constant temperature mixer, add 10 parts of maleic acid modified rosin resin and 15 parts of nano-silica modified epoxy resin in sequence, and stir at 60°C for 2 hours to obtain a mixed solution A; add 6 parts of polyethylene glycol (as an emulsifier), 8 parts of hydrophobic modification liquid, and 8 parts of anti-ultraviolet agent in sequence to the mixed solution A, and stir at 50°C for 1 hour to obtain a coating stock solution;

[0085] S5: Coating process

[0086] The coating stock solution was evenly coated on the surface of the PET resin plate by cast coating method and pre-dried in a fume hood for 30 minutes;

[0087] Apply only once;

[0088] The film was cured at 150° C. for 30 minutes to obtain a solar cell backplane PET resin film.

[0089] [Comparative Example 2]

[0090] S1: Preparation of coating stock solution

[0091] Add the following to the thermomixer:

[0092] 200 parts of anhydrous ethanol (as solvent)

[0093] 25 parts of maleic acid modified rosin resin

[0094] 25 parts of common commercially available silica-modified epoxy resin (without special modification)

[0095] 10 parts polyethylene glycol (as emulsifier)

[0096] 15 parts of commercially available hydrophobic agent (organic silicon hydrophobic agent)

[0097] 15 parts of commercially available UV inhibitor (single UV-531)

[0098] Stir at 60°C for 2 hours to obtain a coating stock solution;

[0099] S2: Coating process

[0100] The coating stock solution was evenly coated on the surface of the PET resin plate by cast coating method and pre-dried in a fume hood for 30 minutes;

[0101] Repeat the coating operation three times;

[0102] The film was cured at 150° C. for 30 minutes to obtain a solar cell backplane PET resin film.

[0103] Compared with Examples 1 and 2, Comparative Example 3 mainly has the following differences:

[0104] Use common commercially available silica-modified epoxy resin without multiple synergistic modifications

[0105] Using a single commercially available silicone hydrophobic agent lacks synergistic effects

[0106] Use a single UV inhibitor instead of optimizing the compound system

[0107] No special modification of silica

[0108] Lack of dedicated preparation steps for hydrophobic modification fluids

[0109] No optimization of anti-ultraviolet agent

[0110] Performance Testing

[0111] The performance test results of the samples obtained in Examples 1 to 2 and Comparative Examples 1 to 2 are listed in Table 1.

[0112] Contact angle test

[0113] Referring to GB / T 30693-2014 “Determination of contact angle of surfactants”, a DSA100 contact angle measuring instrument from Kruss Company of Germany was used, with a test temperature of 23±2°C and a relative humidity of 50±5%.

[0114] Water vapor transmission rate test

[0115] Refer to GB / T 1037-1988 "Determination of water vapor transmission rate of plastic films and sheets", use W3 / 030 water vapor transmission rate tester, test temperature 38±2℃, relative humidity 90±2%.

[0116] Peel strength test

[0117] Refer to GB / T 2790-1995 "Test Method for Peel Strength of Adhesive Tapes", use XLW-50N intelligent electronic tensile testing machine, peeling speed 300mm / min. Before the peel strength retention rate after aging test, 1000h UV aging treatment is required.

[0118] Weathering test

[0119] According to ASTM G154 standard, a xenon lamp aging test box was used, the light intensity at 340nm was 0.89W / m2, the blackboard temperature was 70±3℃, and the relative humidity was 50±5%.

[0120] Heat and humidity test

[0121] The test was conducted under 85°C / 85%RH conditions using a high and low temperature humidity test chamber.

[0122] Table 1

[0123]

[0124] Both Example 1 and Example 2 of the present invention exhibit excellent comprehensive performance. In terms of hydrophobicity, the contact angles reach 115° and 112°, respectively, which are significantly higher than the industry standard requirements, thanks to the multiple synergistic modification effects of modified silica and the optimized hydrophobic modification liquid formula; in terms of water barrier performance, the moisture permeability of the two embodiments is 1.2 and 1.3 g / m2·24h, respectively, which is much better than conventional products, reflecting excellent water vapor barrier performance; in terms of interface bonding, the peel strength of Examples 1 and 2 reaches 8.5 and 8.2 N / cm, respectively, and the strength retention rate after 1000 hours of UV aging is still maintained at more than 90%, indicating that a stable chemical bond is formed between the coating and the substrate; in terms of weather resistance, the UV resistance and moisture and heat resistance of the two embodiments are both more than 2000 hours and 1500 hours, showing excellent environmental adaptability and service life. The realization of these excellent properties is mainly attributed to the multiple synergistic modification technology and optimized process parameters adopted by the present invention.

[0125] In contrast, the performance indicators of Comparative Examples 1 and 3 are significantly lower than those of the embodiment. The contact angles of Comparative Examples 1 and 3 are only 92° and 85°, respectively, indicating that their hydrophobic effects are not ideal; the moisture permeability is as high as 2.8 and 3.5 g / m2·24h, respectively, and they cannot provide good water vapor barrier performance; the peel strength is only 5.1 and 4.2 N / cm, and the strength retention rate after aging drops to 65% and 55%, respectively, indicating that the interface bonding is unstable; the UV resistance can only reach 1200 hours and 800 hours, and the moisture and heat resistance is only 800 hours and 600 hours, which is much lower than the embodiment product. Comparative Example 1 does not use the optimal ratio, and Comparative Example 3 does not use modified silica, so they cannot achieve the ideal performance indicators. It can be clearly seen from the performance comparison that the multiple synergistic modified silica technology, optimized formula design and improved preparation process adopted by the present invention have significant advantages in improving product performance, can meet the strict requirements of solar cell backplanes for high performance and long life, and have important practical application value. These test results fully confirm the innovation and advancement of the present invention, and provide reliable technical support for the industrial application of high-performance solar cell backplane PET resin film.

[0126] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing a PET resin film for a solar cell backplane, characterized in that: The PET resin film comprises a PET resin plate and a composite coating, wherein the composite coating comprises the following components in parts by weight: 15-30 parts of maleic acid modified rosin resin; 20-30 parts of nano-silicon dioxide modified epoxy resin; 10-20 parts of hydrophobic modification liquid; 14-18 parts of anti-ultraviolet agent; Emulsifier 8-12 parts; The preparation method comprises: S100: preparing a coating stock solution of the composite coating; S200: applying the coating stock solution to the PET resin plate; S300: Drying to obtain a PET resin film for a PET back sheet of a solar cell.

2. The method for preparing a PET resin film for a solar cell back sheet according to claim 1, characterized in that: The step S100 specifically includes: S101: adding anhydrous ethanol or butyl acetate to a constant temperature mixer, and then adding the maleic acid-modified rosin resin and the nano-silica-modified epoxy resin mixture to obtain a mixed solution A; S102: adding the emulsifier, the hydrophobic modification liquid, and the anti-ultraviolet agent into the mixed solution A to obtain the coating stock solution.

3. The method for preparing a PET resin film for a solar cell back sheet according to claim 2, characterized in that The hydrophobic modified liquid is obtained by compounding modified silicon dioxide, calcium gluconate and ultrapure water.

4. The method for preparing a PET resin film for a solar cell back sheet according to claim 2, characterized in that The anti-ultraviolet agent is obtained by compounding a UV series ultraviolet absorber and a BP series ultraviolet absorber.

5. The method for preparing a PET resin film for a solar cell back sheet according to claim 2, characterized in that The emulsifier is selected from one of polyethylene glycol, Tween 80 and carboxymethyl cellulose.

6. A method for preparing a PET resin film for a solar cell back sheet according to any one of claims 1 to 5, characterized in that: The preparation method of the anti-ultraviolet agent is as follows: a UV absorber UV-9 whose main component is 2-hydroxy-4-methoxybenzophenone and a UV absorber BP-2 whose main component is 2,2',4,4'-tetrahydroxybenzophenone are compounded in a ratio of 1.2:

1.

7. A method for preparing a PET resin film for a solar cell back sheet according to any one of claims 1 to 5, characterized in that: The hydrophobic modified liquid is obtained by mixing the modified silicon dioxide, the calcium gluconate and the ultrapure water in a ratio of 5:1:

94.

8. The method for preparing a PET resin film for a solar cell back sheet according to claim 3, characterized in that The modified silicon dioxide is obtained by co-modifying the nano silicon dioxide with tridecafluorooctyltrimethoxysilane, vinyltrimethoxysilane and methacryloxyethyltrimethylammonium chloride.

9. The method for preparing a PET resin film for a solar cell back sheet according to claim 8, characterized in that: The preparation steps of the modified silicon dioxide include: S401: Under nitrogen blowing, 1-5 parts by mass of the nano-silicon dioxide is transferred into a solid phase synthesis tube and anhydrous ethanol is added; S402: adjusting the pH value of the solution in the synthesis tube to 4-5 by dropwise adding dilute acetic acid, adding 1-5 parts by mass of the tridecafluorooctyltrimethoxysilane and 2-5 parts by mass of the vinyltrimethoxysilane, respectively, and reacting at 50-60° C. for 6-8 hours to obtain co-grafted silica; S403: adding deionized water or anhydrous ethanol to the synthesis tube to alternately wash the co-grafted silica for 2-3 rounds to remove the reaction reagents, adding anhydrous ethanol and blowing the co-grafted silica evenly with nitrogen; S404: The pH value of the solution in the synthesis tube is adjusted to 4-5 by dropping dilute acetic acid, 2-5 parts by mass of methacryloyloxyethyl trimethyl ammonium chloride is added, and the reaction solution is discarded after reacting at 50-60°C for 4-5 hours, and deionized water or anhydrous ethanol is added to the synthesis tube for 2-3 rounds of alternating washing, and nitrogen is blown for 1-1.5 hours, and then the tube is transferred to a 60°C vacuum drying oven for drying to obtain the modified silica.

10. A method for preparing a PET resin film for a solar cell back sheet according to any one of claims 1 to 5, characterized in that: The step S300 specifically includes: S301: using a cast coating method or a roller coating method, repeatedly coating the coating solution three times on the surface of the PET resin plate; S302: After coating, pre-dry in a fume hood for 30 minutes; S303: Curing at 150°C for 30 minutes to form a dense coating.